Modulation of extrasynaptic GABAA alpha 5 receptors in the ventral hippocampus normalizes physiological and behavioral deficits in a circuit specific manner - J. J. Donegan (Nature Portfolio, 2019)
Region-specific increases in hippocampal activity have been reported in schizophrenia patients, yet there are little known about how these circuit levels changes modulate behavioral deficits. Here authors found that that over-expression of the a5 subunit of the GABAA receptor increased tonic GABA currents and normalized aberrant pyramidal cell activity in the ventral hippocampus which had distinct disease symptom outcomes depending on the pathway targeted